Being an Authentic Christian: an Analysis Based on The Philosophy of Søren Kierkegaard - Shelomita Selamat (International Journal of Indonesian Philosophy & Theology, 2021)
Kierkegaard emphasis the importance of each individual being an authentic person. In his works, he gives an overview and direction to become an authentic person. Realizing whether someone authentically is not easy. Nowadays, I see many Christians who do not really live their lives as a Christian. The focus of this research is to present Kierkegaard's view on the criteria of an authentic Christian. The method used is a critical reading analysis of Kierkegaard's works (particularly Purity of Heart and The Sickness unto Death), previous research studies, observations, and interviews with several individuals. The author finds six criteria about authentic Christian individuals, namely: (1) Living in repentance, (2) Personal relationship with God, (3) Fear of God, (4) Willingness to suffer, (5) Being a loving person, and (6) Living in silence.